ANALISIS PREDIKSI FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI DENGAN MENGGUNAKAN MODEL ALTMAN, OHLSON DAN SPRINGATE (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2016)
This study aims to determine the results of prediction of financial distress in the food and beverage company using Altman model, Ohlson and Springate in the period 2012-2014 for financial data obtained from the Indonesia Stock Exchange. This study using purposive sampling techniques and the results there are 12 companies that meet the criteria. The results using Altman model years 2012- 2014 there is one company that is experiencing financial distress. Then the prediction results by using models Ohlson in 2012 there was one company predicted financial distress. In 2013 there were experiencing financial distress and in 2014 there are two companies predicted to experience financial distress. The next prediction results by using the model years 2012-2014 Springate there are 2 companies experiencing financial distress.Keywords: Financial distress, Altman, Ohlson, Springate, Bankruptcy